San Francisco - Panama - 1915 - March - Damasus G. Gallur::::::::: (Gallur & Co.)
Piano score, 6 p. Following title: Dedicated to the Panama-Pacific International Exposition, 1915, San Francisco, California At head of title on cover: Popular edition. On verso of least leaf: Compliments of Hauschildt Music Company, San Francisco and Oakland.